The Impact of Water Quality on GDP Growth : Evidence from Around the World - Desbureaux, Sebastien; Damania, Richard; Rodella, Aude-Sophie; Russ, Jason; Zaveri, Esha (World Bank, Washington, DC, 2019)
Declining water quality can impact the economy in various ways. Impacts can be found in the health sector, where labor productivity can be affected, in agriculture, where the quality and quantity of food produced can be reduced, and in tourism, real estate, aquaculture/fisheries and other sectors which rely on environmental quality and ecosystem services. Despite these well-known impacts, finding economy-wide affects of water quality on economic activity can be elusive. In this paper we attempt to fill this gap by using a conventional empirical approach in contemporary environmental economics and new data on economic activity and water quality for nineteen countries from 1990-2014. The authors find that when rivers become very heavily polluted, regions downstream see reductions in economic growth, losing between 0.8 and 2.0 percent of economic growth. These losses imply that in many places, the costs of environmental degradation are severely under-estimated and well above efficient levels.